KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp.) DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KABUPATEN KAMPAR - Febriyanti, Fani; Yoza, Defri; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The forest in Indonesia has various natural resources. One of the natural resources is nepenthes. One of the forests which has nepenthes is the prohibition forest of rumbio customary in rumbio village. The prohibition forest of rumbio customary rumbio village is the highest heritage of the society of rumbio village culture. It has various natural resources and the flora and the fauna in this area. The methods used were belt transect method and purposive sampling method. It was found out that there are three types of nepenthes in the prohibition forest of rumbio customary rumbio village; they are: Nepenthes ampullaria, Nepenthes gracillis, and Nepenthes mirabilis. The diversity index of nepenthes in the prohibition forest of rumbio customary rumbio village at Kuyang yard zone was in the amount of 0,374, Sialang Layang zone was in the amount of 0,653 and Panoghan zone was in the amount of 0,808 in which three of them are categorized into low. Keywords: The prohibition forest of rumbio customary rumbio village, Diversity Index, nepenthes, Kuyang yard zone, Sialang layang zone, Panoghan zone.